Negotiating the Waves and Tides of Life: Challenges, Opportunities, and Coping of Skimboarders in Dahican, Mindanao, Philippines - Ceniza, Chris Lloyd A. (ASEAN Journal on Hospitality and Tourism, 2025)
Employing qualitative methods, particularly phenomenological research designs, this study explored the lived experiences and coping strategies of skimboarders in Dahican, Mindanao.  Studies have shown varying effects of ecotourism on locals.  In this study, the result shows the existence of affirmative and negative effects of tourism. Skimboarders faced physical struggles in learning the sport due to its technical difficulty, high temperatures, and exhaustion.  On the emotional and psychological struggles, dealing with unforgiving tourist who treats them as mere commodities or human beings being paid to serve at their disposal.  The wanton abuse of the environment, where tourists are inconsiderate of leaving trash anywhere along the coastlines.  On the other hand, the result also showed an affirmative effect on skimboarders.  Among these were livelihood chances. The tourism industry provides income for skimboarders through tutorials, and these fees are used for their daily expenses.  Further, improved interpersonal relations also appeared.  By dealing with tourists, skimboarders developed their skills in customer relations. Lastly, they improved their advocacy for the environment through marine life protection.  Coastal clean-ups and the development of turtle hatcheries increase their love for the environment, especially the sea.  The result of this study greatly contributes to the growing knowledge and literature on the lives of skimboarders by understanding their opportunities and challenges.